Of Mice and Culture: How Beliefs About Knowing Affect Habits of Thinking - Morio, Hiroaki; Yeung, Saiwing; Peng, Kaiping; Yamaguchi, Susumu (Frontiers in Psychology, 2022)
Recent research suggests that individuals from East Asian and Western cultures differ in the degree to which they hold a folk world view known as naïve dialecticism, which is characterized by tolerance for contradiction, expectation of change, and cognitive holism. The current research utilizes the Mouse Paradigm to investigate the dynamic nature of naïve dialecticism in real time by measuring individuals’ fluctuations in judgment during the process of contemplation. The results showed cultural differences in dynamic measures of evaluation process: Japanese participants took more time to stabilize their thought and showed more fluctuations in their judgment than American participants. These cultural differences were fully mediated by individual differences in levels of naïve dialecticism as measured by the level of dialectical self-views. Implications for cultural psychology and the psychology of dialectical thinking are discussed.